THREE CRITICAL APPROACHES IN LITERARY CRITICISM: AN EXAMPLE ANALYSIS ON MATTHEW ARNOLD’S DOVER BEACH - Anik Cahyaning Rahayu (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2019)
To approach a work of literature can be done in different ways. Some approaches can be used to analyze a literary work, such as psychological, historical, sociological, etc. To analyze one literary work, more than one approach can be applied. This article is an example of analyzing a poem, Mattew Arnold's Dover Beach from three different critical positions, the formalist, the sociological, and psychoanalytical. The formalist critics view work as a timeless aesthetic object. We may find whatever we wish in the work as long as what we find is in the work itself The sociological critic views that to understand Arnold’s ‘Dover Beach’, we must know something about the major intellectual social current of Victorian England and how Arnold responded to them. All psychoanalytic critics assume that the development of the psyche in humans is analogous to the development of the physique. ‘Dover Beach’ is richly suggestive of the fundamental psychic dilemma of man in civilization.